2018
DOI: 10.4103/ua.ua_104_17
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ultrasound-guided percutaneous suprapubic cystostomy in resource-poor setting: A 7-year review

Abstract: Introduction:Percutaneous cystostomy techniques are usually done using disposable sets in developed countries which are not affordable in poor-resource settings. However, the percutaneous technique can be done using reusable trocar or selected big size surgical blades. This is simple, safe, and cost effective in poor-resource setting. The procedure is best done under ultrasound guidance but can also be done blindly in select cases. We present our 7-year experience in ultrasound-guided percutaneous suprapubic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
2
2
1
1
Order By: Relevance
“…14 Muhammad et al, reviewed 07 years complications of ultrasound guided SPC and reported stoma bleeding and hematuria in 01 (0.7%) patient and 02 (1.5%) required revision of SPC due to catheter displacement. 15 However, in our study, 05 (16.7%) patients developed complication in C-SPC group, which needed their SPC revision (pvalue <0.019) and only single attempt for SPC was successful in US-SPC group and no patients required SPC revision or developed complications such as hematuria or stoma bleeding.…”
Section: Discussioncontrasting
confidence: 52%
“…14 Muhammad et al, reviewed 07 years complications of ultrasound guided SPC and reported stoma bleeding and hematuria in 01 (0.7%) patient and 02 (1.5%) required revision of SPC due to catheter displacement. 15 However, in our study, 05 (16.7%) patients developed complication in C-SPC group, which needed their SPC revision (pvalue <0.019) and only single attempt for SPC was successful in US-SPC group and no patients required SPC revision or developed complications such as hematuria or stoma bleeding.…”
Section: Discussioncontrasting
confidence: 52%
“…No complication was detected in any patient in the immediate and 2-week follow-up [3]. In another study, it was reported that the USG-assisted technique was simple, safe, effective and associated with minimal complications [8]. In two studies comparing direct blind and USG-assisted techniques in the literature, the ultrasonography procedure was found to be safer, which is consistent with our study [5,6].…”
Section: Discussionsupporting
confidence: 89%
“…Causes of urinary retention include benign prostatic hyperplasia (BPH), urethral stricture, prostate cancer, clot retention, stone and neurological bladder [7]. In two studies reported in the literature, urethral stricture and BPH were determined as the most common causes of urinary retention in patients with PSCC, respectively, and there was only one female patient in both study populations [5,8]. Similarly, the most common etiological factor in our series was urethral stricture, and the second was BPH.…”
Section: Discussionsupporting
confidence: 55%
“…After filling the bladder, the whole body was placed in 30° Trendelenburg position. Subsequently, color Doppler ultrasound [7] was used to select the appropriate puncture point on the pubic symphysis and confirm; there was no intestinal canal or vasculardense area in the puncture area. For patients with benign prostatic hyperplasia, it was necessary to confirm that there was no hyperplastic prostate tissue in the puncture area.…”
Section: Surgery Techniquesmentioning
confidence: 99%